The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0079-6611(03)00026-0
|View full text |Cite
|
Sign up to set email alerts
|

The diffusive regime of double-diffusive convection

Abstract: The diffusive regime of double-diffusive convection is reviewed, with a particular focus on issues that are holding up the development of large-scale parameterizations. Some of these issues, such as interfacial transports and layer-interface interactions, may be studied in isolation. Laboratory work should help with these. However, we must also face more difficult matters that relate to oceanic phenomena that are not easily represented in the laboratory. These lie beneath some fundamental questions about how d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 130 publications
10
189
0
2
Order By: Relevance
“…Schmitt 1994;Ruddick 1997;Kelley et al 2003) to adopt the one-component Phillips-Posmentier conceptualization to double-diffusive layering. The Phillips-Posmentier model captures only one aspect of the problem -the ρ z effect (figure 2a).…”
Section: ) Wherementioning
confidence: 99%
“…Schmitt 1994;Ruddick 1997;Kelley et al 2003) to adopt the one-component Phillips-Posmentier conceptualization to double-diffusive layering. The Phillips-Posmentier model captures only one aspect of the problem -the ρ z effect (figure 2a).…”
Section: ) Wherementioning
confidence: 99%
“…Due to limited vertical resolution, it is unclear whether there are occurrences of split layers that appear to form and re-merge in hours, or whether the observations are indicating thickness changes in layers. Split layers are commonly observed in oceanographic profiles from other regions (Kelley et al, 2003). Kelley (1988) suggested that staircase layer thickness is controlled by layer splitting where new layers are formed from existing interfaces.…”
Section: A Sub-inertial Motion At Site D I Deep Water Columnmentioning
confidence: 99%
“…While the early laboratory experiments tended to support the 4/3 flux law (e.g. Schmitt 1979a) within the margins of the experimental and statistical error, questions have been raised with regard to its generality (Kelley et al 2003). The laboratory values of C S have been found to overestimate the oceanic fluxes by at least an order of magnitude, a discrepancy that may indicate that the effective exponent of the flux law realized in the oceanic conditions exceeds 4/3.…”
Section: Flux Lawsmentioning
confidence: 99%